2021
DOI: 10.26656/fr.2017.5(2).552
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, microbiological and sensory characteristics of cow’s milk Kashkaval cheese ripened at different temperatures

Abstract: Kashkaval is a hard cheese produced in Eastern Europe and consumed after ripening. The influence of ripening temperature (9±1°C, 11±1°C and 13±1°C) of cow's milk Kashkaval cheese on its physicochemical, microbiological and sensory characteristics was studied. For the ripening period no statistically significant differences (P>0.05) in the indicators dry matter, fat content, salt and protein were found. A slight decrease in active acidity was observed during the maturation process which tendency was more pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The acidity of Ras cheese which contains microcapsules was significantly (p < 0.05) higher than control cheese during ripening and until the end of the ripening period. Similar results were by Ivanova et al (2021) that showed a slight decrease in 4. The TN content in all of the experimented Ras cheeses gradually increased with the advancement of the ripening period due to the decrease in the moisture contents in the cheese.…”
Section: Physicochemical Evaluations Of Ras Cheese During Ripeningsupporting
confidence: 86%
“…The acidity of Ras cheese which contains microcapsules was significantly (p < 0.05) higher than control cheese during ripening and until the end of the ripening period. Similar results were by Ivanova et al (2021) that showed a slight decrease in 4. The TN content in all of the experimented Ras cheeses gradually increased with the advancement of the ripening period due to the decrease in the moisture contents in the cheese.…”
Section: Physicochemical Evaluations Of Ras Cheese During Ripeningsupporting
confidence: 86%
“…Survival of nonstarter microflora in Kashkaval cheese with different salt concentrationsSimilar conclusions about the nonstarter microflora of cow's milk Kashkaval cheese ripened at different temperatures were drawn by Ivanova et al[34].…”
mentioning
confidence: 60%